The art of teaching - Parini, Jay (Oxford University Press, 2005)
Writer and critic Parini looks back over his own decades of trials, errors, and triumphs, in a memoir replete with hard-won wisdom about the teacher's craft for instructors of all levels. He offers valuable insight into the many challenges that educators face, from establishing a persona in the classroom, to fostering relationships with students, to balancing a teaching load with academic writing and research.